Optimization of ion exchange cryogel functionalization via the epoxy method for protein adsorption from ora-pro-nobis (Pereskia aculeata) - Mendes, Mariana Oliveira; de Oliveira Meira, Ana Cristina Freitas; Mól, Paula Chequer Gouveia [UNESP]; Neves, Isabelle Cristina Oliveira; Minim, Luis Antonio; de Resende, Jaime Vilela; Veríssimo, Lizzy Ayra Alcântara (Wiley, 2025)
Ora-pro-nobis (OPN) is a plant with a high protein content. The development of new adsorbents that enable the separation of biomolecules while preserving their bioactivity has attracted the interest of researchers. This work reports the functionalization of cryogel via the epoxy method and its application in the adsorption of OPN proteins through ion exchange, using amino acids. Among the pH values and types of ion exchange ligands evaluated (cysteine, taurine, polyethyleneimine, and glutamic acid), the highest adsorption of OPN proteins (54.44 mg g−1) was observed at pH 5.5 for the cryogel functionalized with glutamic acid (cryogel-GA). The optimal conditions for cryogel functionalization were obtained at 50°C for 28 h, with an adsorption capacity of 103.37 ± 4.60 mg g−1. The effective bonding between glutamic acid's carboxylic/amine groups and the cryogel's epoxy groups increases adsorption site density. The cryogel-GA retained high porosity (0.92%) and water retention capacity, crucial for protein purification from crude extracts. The Langmuir model was fitted to the equilibrium adsorption isotherms, with a maximum adsorption capacity of 76.34 mg g−1 at 8°C, 172.41 mg g−1 at 15°C, 252.56 mg g−1 at 25°C, and 400 mg g−1 at 35°C. OPN protein adsorption on cryogel-GA increased with temperature. Thermodynamic analysis based on the Van't Hoff relationship indicated that the process was spontaneous ((Formula presented.) = −18.03 kJ mol−1 at 35°C) and entropically driven, confirming its feasibility. These results demonstrate that cryogel-GA is a promising matrix for ion exchange protein capture processes.
Keywords: adsorption; ion exchange; isotherms; ora-pro-nobis; protein